2021
DOI: 10.1371/journal.pone.0250584
|View full text |Cite
|
Sign up to set email alerts
|

A phylogenetic study of the members of the MAPK and MEK families across Viridiplantae

Abstract: Protein phosphorylation is regulated by the activity of enzymes generically known as kinases. One of those kinases is Mitogen-Activated Protein Kinases (MAPK), which operate through a phosphorylation cascade conformed by members from three related protein kinase families namely MAPK kinase kinase (MEKK), MAPK kinase (MEK), and MAPK; these three acts hierarchically. Establishing the evolution of these proteins in the plant kingdom is an interesting but complicated task because the current MAPK, MAPKK, and MAPKK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…MPKs in general have a highly conserved sequence in which many domains have been identified that can be used to distinguish between different groups of MPKs in green plants (González‐Coronel et al, 2021; Jonak et al, 2002 ) . Group A MPKs (to which MPK3/6 orthologs belong) were reported to be present in many plant species including the fern S. cucullata but not the lycophyte S. moelendorfii or the bryophytes P. patens and M. polymorpha ( González‐Coronel et al, 2021). Our analyses confirmed these findings; top BLAST hits with AtMPK3/6 sequence in the more primitive plants were more like group B MPKs.…”
Section: Mpk3 and 6 Proteins Date Back To Fernsmentioning
confidence: 99%
See 1 more Smart Citation
“…MPKs in general have a highly conserved sequence in which many domains have been identified that can be used to distinguish between different groups of MPKs in green plants (González‐Coronel et al, 2021; Jonak et al, 2002 ) . Group A MPKs (to which MPK3/6 orthologs belong) were reported to be present in many plant species including the fern S. cucullata but not the lycophyte S. moelendorfii or the bryophytes P. patens and M. polymorpha ( González‐Coronel et al, 2021). Our analyses confirmed these findings; top BLAST hits with AtMPK3/6 sequence in the more primitive plants were more like group B MPKs.…”
Section: Mpk3 and 6 Proteins Date Back To Fernsmentioning
confidence: 99%
“…We highlight separately one domain which is characteristic for Group A&B MPKs. This domain is thought to participate in the selection of the MPK substrate because it is predicted to be on the outside of the folded protein (domain 12 in González-Coronel et al, 2021). Additional recognized sequences with a proposed function are the docking motif and the activation domain.…”
Section: Mpk3 and 6 Proteins Date Back To Fernsmentioning
confidence: 99%
“…This activates the GTPase Ras, which then binds to and activates Raf, which serves as a MAPK kinase kinase (MKKK), phosphorylating and activating a MAPK kinase MEK, which then phosphorylates and activates a MAPK (originally named extracellular signal regulated kinase; ERK) (Terrell & Morrison, 2019). Reflecting the expansion of the protein kinase family in the plant kingdom, there are 20 MAPKs, 10 MKKs, and 80 MKKKs in Arabidopsis (González-Coronel et al , 2021) – many more than in mammals. Despite their number, very little is known about MKKKs.…”
Section: Introductionmentioning
confidence: 99%
“…Sequence homology defines three distinct subclasses known as MKKK, ZIK, and Raf-like kinases. There are 48 Raf-like kinases in Arabidopsis, divided into eleven subfamilies: B1-B4 and C1-C7 (Jonak et al , 2002; González-Coronel et al , 2021). Phylogenetic analyses indicate that plant Raf-like kinases do not cluster with metazoan MKKK or Raf kinases (Tang & Innes, 2002; Champion et al , 2004) and are considered a plant (Pl)-specific family of tyrosine kinase-like (TKL) proteins (TKL-Pl-4) (Lehti-Shiu & Shiu, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation